Development of Problem Based Learning Model on the History of Reform Learning to Improve the Democratic Attitude of Sabillah Sampang SMA Students - Rohman, Fathu Shodiqur; Pelu, Musa; Sudiyanto, Sudiyanto (Budapest International Research and Critics University, 2022)
The implementation of reform education for students is very useful in fostering students' democratic attitudes, but in fact the process of implementing reform education is still a concern. Judging from the results of pre-research studies at Sampang Public High Schools, there are only 35% of students who have an awareness of the importance of democracy, and the remaining 65% of students are indifferent and reluctant to be involved in democratic activities. The contributing factor is the influence of everyday online games that cause moral and moral imbalances in students, so this is what fosters individualistic character, not with the surrounding environment, and lack of self-awareness to actively organize. Therefore, the teacher's role in increasing awareness of democracy in students can also be done by developing emotional, intellectual, social, kinesthetic, and spiritual intelligence possessed by these students in everyday life. This study uses a qualitative method with the sampling technique in this study is multistage sampling. The objectives of this research are; (1) To analyze the previous implementation of democracy that has been implemented in SMA Sabillah Sampang. (2) To describe the effectiveness of the implementation of reformation history learning at SMA Sabillah Sampang. (3) To analyze the implementation of the previous history learning development model that was used in Sabillah Sampang High School which was running effectively. (4) To analyze the humanistic approach chosen to improve the democratic attitude of Sabillah Sampang High School students, and (5) To analyze whether or not the development of the historical reform learning model using discovery learning is feasible.